Entre reductionnisme et antipositivisme - Alexandru GAFTON (Diversitate si Identitate Culturala in Europa)
As a continuous result of evolutive and adaptive diversifications, reality derives from principles that generate differentiated laws which concretize the matter in specific and particular structural and functional ways. Sciences, in their turn, by means in which human mind seeks to acquire knowledge, are bound to comply with reality orienting their methods of observation, examination and conceptualization, according to their abilities to gain acces to teh foundations and development of reality – criterion by which they are ordered.